Respiratory homeostasis features in female students with idiopathic arterial hypotension and hyperventilation syndrome - L. M. Soltysik; V. A. Levchenko (Zaporožskij Medicinskij Žurnal)
Aim. To assess the condition of pulmonary ventilation and diaphragmatic excursion in female students with idiopathic arterial hypotension in the context of hyperventilation syndrome and excessive anxiety.